Pharmacokinetics, Tissue Distribution, Metabolism, and Excretion of Naringin in Aged Rats - Zeng, Xuan; Su, Weiwei; Zheng, Yuying; He, Yudong; He, Yan; Rao, Hongyu; Peng, Wei; Yao, Hongliang (Frontiers in Pharmacology, 2019)
Aging is an inevitable biological process characterized by the loss of functional capacity and associated with changes in all phases of pharmacokinetic processes. Naringin, a dietary flavanone glycoside, has been proved to be beneficial for the treatment of multiple age-associated chronic diseases. To date, the pharmacokinetic processes of naringin in aged individuals are still unknown. Thus, a rapid resolution liquid chromatography tandem triple quadrupole mass spectrometry (RRLC-QQQ-MS/MS) method was established for the determination of naringin and its metabolite naringenin in rat plasma, urine, feces, and tissue homogenate. The pharmacokinetic parameters were calculated and a higher exposure of naringin and naringenin were observed in aged rats. Naringin and naringenin were mostly distributed in gastrointestinal tract, liver, kidney, lung, and trachea. Furthermore, a total of 39 flavonoid metabolites (mainly glucuronides and sulfates) and 46 microbial-derived phenolic catabolites were screened with ultra-fast liquid chromatography-quadrupole-time-of-flight tandem mass spectrometry (UFLC-Q-TOF-MS/MS). Naringenin, hippuric acid, and 3-(4'-hydroxyphenyl)propionic acid were predominated metabolites. This study systemically investigated the pharmacokinetics, tissue distribution, metabolism, and excretion of naringin in aged rats, revealing age- and gender-related changes in the in vivo behavior of naringin. These results would be helpful for the interpretation of pharmacokinetics and pharmacodynamics of naringin in aged population.